Spatiotemporal modeling and simulation of chernobyl radioactive fallout in northern Turkey - Niksarlioglu, Secil; Kulahci, Fatih; Sen, Zekai (Springer, 2015)
In this study, the Chernobyl radioactive fallouts are described through the spatio-temporal point cumulative semivariogram (STPCSV) method, which is used to identify spatial and temporal regionalized changes in Cs-134 and Cs-137 concentrations. The application of the methodology is presented for the Black Sea Region, which is the most affected area from the Chernobyl radioactive fallouts in Turkey. After detailed explanation of the methodology hourly simulation maps are prepared for Cs-134 and Cs-137 spreads over the area. Each one of these maps provides valuable information about the spatial variability of the concentrations concerned. The STPCSV helps to identify the exhibition of heterogenic structure of radioactive concentration in the study area.
Keywords: Radioactive fallout; Spatial analysis; Spatiotemporal analysis; Model